Strain-induced quantum spin Hall effect in methyl-substituted germanane GeCH(3) - Ma, Yandong (Sci Rep, 2014)
Quantum spin Hall (QSH) insulators exhibit a bulk insulting gap and metallic edge states characterized by nontrivial topology. We investigated the electronic structure of an isolated layer of methyl substituted germanane GeCH(3) by density functional calculations (DFT), and its dynamic stability by phonon dispersion calculations. Our results show that an isolated GeCH(3) layer has no dynamic instability, and is a QSH insulator under reasonable strain. This QSH insulator has a large enough band gap (up to 108 meV) at 12% strain. The advantageous features of this QSH insulator for practical room-temperature applications are discussed.